Frihetsberövade på olika villkor - En rättslig jämförelse mellan riskbaserade påföljder: Säkerhetsstraffet och rättspsykiatrisk vård med särskild utskrivningsprövning - Jönsson,Emilia (2025)
During the summer of 2022, the Swedish government decided to initiate an inquiry with the aim of reforming certain aspects of criminal law. The proposed reforms sought to prevent recidivism, enhance public safety, and impose stricter measures on offenders who fail to comply with the conditions of their sentence. One of the inquiry’s most central elements was the proposal for a security sentence (“säkerhetsstraff”) – a new type of indefinite custodial sanction. The security sentence is intended to apply to individuals who relapse into serious crime after having previously served a custodial sentence or is convicted on a single occasion for repeated criminal conduct. It aims to extend the deprivation of liberty as along as the risk of further offences remains. It is only when such a risk no longer exists that the possibility of release arises. Indefinite deprivation of liberty is not entirely unfamiliar within the Swedish legal system. Currently, there is a sanction of such nature, aimed at individuals who are assessed to pose a risk of reoffending in serious criminal activity. The primary distinction, relative to proposed security sentence, lies in its area of applicability, as this existing sanction solely applies to individuals with a severe mental disorder. Known as forensic psychiatric care with special discharge review (“Rättspsykiatrisk vård med särskild utskrivningsprövning”), this measure targets individuals who have committed crimes under the influence of a severe mental disorder and are considered to pose a continued risk of committing serious offences. The purpose of this thesis has been to examine and analyse two criminal sanctions with similar motivations – the security sentence and forensic psychiatric care with special discharge review –in relation to each other and to the principles of legal certainty and equality before the law. Using the legal analytical method, the thesis has reviewed the structure and applicability of the relevant legislation, the underlying legislative motives, and the opinions expressed by referral bodies. This investigation identified four central themes that have been subject to particularly thorough analysis: 1) which individuals are subject to each sanction, 2) the criteria for the imposition of the sanctions, 3) the duration of the sanctions as well as the conditions for their termination and 4) the risk assessments that serve as the basis for both deprivation of liberty and release. The analysis demonstrates that both sanctions suffer from significant deficiencies in terms of predictability, especially regarding the duration of deprivation of liberty and the criteria for release. This presents a serious challenge to the principle of legal certainty. Furthermore, it becomes apparent that individuals with similar criminal backgrounds are afforded varying levels of legal certainty depending on whether they are assessed as having a severe mental disorder, which undermine the principle of equality before the law.
Keywords: Straffrätt; säkerhetsstraff; rättspsykiatrisk vård med särskild utskrivningsprövning; rättssäkerhet; likhet inför lagen.